DETERMINATION OF PARAMETERS OF METALLIC RESONATOR OF VIBRATORY GYROSCOPE BY ACOUSTIC METHOD - В. Г. Цірук (Вісник Черкаського державного технологічного університету, 2018)
The results of the development and determination of parameters of hightech, cheap coriolis vibratory gyroscope, which provides high accuracy of measurements and is not inferior to the characteristics of its main competitors: fiber-optic and laser gyroscopes, are presented in the work. It is shown that in order to increase the productivity and to reduce the cost of resonator manufacturing, it should be made of metal. The acoustic method is proposed, which allows to determine the Q-factor of different types of oscillations for an arbitrary number of heterogeneities, depending on their location in the resonator, as well as the parameters of the Q-factor of the resonator itself. The correctness of the heat treatment operations and the heterogeneity of mass distribution along cohesive coordinates of the resonator, as well as the possibility of using resonators at subsequent stages of assembling are evaluated.